The Application of Politeness Strategies ByTeenagers In Mostaganem - Khedim, Rachida (My University, 2020)
This research paper aims to study linguistic politeness, taking a variety of Algerian Arabic, namely Mostaganem in the region of Khadra as case study. The study is motivated by two research questions. First, Do Khadra’s teenagers use the same politeness strategies as proposed by Brown& Levinson 1987?. Second, Do Khadra’s teenagers take the social dimension and age into consideration? It is hypothesized that Khadra’s teenagers might use the same politeness strategies as proposed by Brown& Levinson 1987. Also, the social dimension and age might token into consideration while using politeness strategies by the teenagers of Khadra region. Qualitative research was conducted for the collection of data. In this case observation is one of the best ways to collect the data needed. The participants in this investigation are teenagers from Khadra Township. Analysis of data showed that, there is a high applicability between politeness strategies used by teenagers of Khadra speech community and politeness strategies as proposed by Brown and Levinson 1987.
Case study : Khadra Region
Keywords: Linguistic politeness; Brown and Levinson politeness strategies; Khadra Township